Africa's rural youth in the global context - Mueller, Valerie; Thurlow, James; Rosenbach, Gracie; Masias, Ian (International Food Policy Research Institute, 2019)
Governments in Sub-Saharan Africa are under enormous pressure to create more and better jobs for the region’s young and rapidly growing population.1 Africa is undergoing a ‘youth bulge’ in which the share of young people in the working age population is peaking due to past declines in mortality coupled with persistently high fertility (Canning, Raja, and Yazbeck 2015). This demographic transition has created a sense of urgency, and even anxiety, within national governments and the international development community (Resnick and Thurlow 2015). With the advent of the Sustainable Development Goals (UNDESA 2016), most policies and strategies in Africa today focus on promoting ‘inclusive growth’, which means that the population, especially the poor, should not only benefit from, but also participate in, the development process. This has made job creation a major policy objective, alongside the more traditional goals of accelerating economic growth and reducing poverty and hunger.